Współczesny wielowarstwowy krajobraz cyberbezpieczeństwa i pojawiające się nano-zagrożenia. Przegląd - Olszewski, Bogusław (Studia Krytyczne/Critical Studies, 2022)
Presented article attempts to identify the key node located in the three-tier model of cyberspace, the node which is characterized by the greatest potential impact on the other elements essential for the functioning of the whole network, especially in the security context. Based on the network analysis, it was proposed to place the ‘persona’ in the center of interest, in other words the human factor. In this way – regardless of the future direction of the further development of artificial intelligence – an individual adversary is able to dispose the historically unprecedented ability to put an impact on the critical and – potentially – military infrastructure of the state. Thus, individual digitally-skilled person is capable of destabilizing the post-industrial society not only in the context of network/computer security, but also physical security (through the cyber-physical systems).